Moyamoya Disease: A Rare Entity Report Of One Case - Saha, Anup Kumar; Banik, Gobinda (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11423 J Bangladesh Coll Phys Surg 2012; 30: 114-115